2015
DOI: 10.1371/journal.pone.0114933
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effect of a Marine Bacterium on Aquatic Organisms and Its Algicidal Substances against Phaeocystis globosa

Abstract: Harmful algal blooms have caused enormous damage to the marine ecosystem and the coastal economy in China. In this paper, a bacterial strain B1, which had strong algicidal activity against Phaeocystis globosa, was isolated from the coastal waters of Zhuhai in China. The strain B1 was identified as Bacillus sp. on the basis of 16S rDNA gene sequence and morphological characteristics. To evaluate the ecological safety of the algicidal substances produced by strain B1, their toxic effects on marine organisms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Those exceptions present some interesting biological characteristics. For example, several Bacillus strains exhibit strong killing activity against the marine algae Phaeocystis globose , Cochlodinium polykrikoides (now renamed Margalefidinium polykrikoides ) or Chattonella marina (Jeong et al, 2003; Kim et al, 2009; Yang et al, 2015). A strain of Streptomyces iranensis can kill the green alga Chlamydomonas reinhardtii by means of its metabolic product azalomycin F, whilst this algicidal activity can be eliminated by a lichen‐like association between Aspergillus nidulans and C. reinhardtii (Krespach et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Those exceptions present some interesting biological characteristics. For example, several Bacillus strains exhibit strong killing activity against the marine algae Phaeocystis globose , Cochlodinium polykrikoides (now renamed Margalefidinium polykrikoides ) or Chattonella marina (Jeong et al, 2003; Kim et al, 2009; Yang et al, 2015). A strain of Streptomyces iranensis can kill the green alga Chlamydomonas reinhardtii by means of its metabolic product azalomycin F, whilst this algicidal activity can be eliminated by a lichen‐like association between Aspergillus nidulans and C. reinhardtii (Krespach et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been devoted to the investigation of environmental conditions that regulate the occurrence and maintenance of P. donghaiense blooms and the cellular responses of this dinoflagellate to different conditions, such as N/P repletion, N/P depletion, different N/P substrates, acidification, and eutrophication (25)(26)(27)(28)(29). Although many algicidal bacteria have been identified and exploited in the control of Microcystis aeruginosa (5,7,14,17,30), Alexandrium tamarense (9,12,18,19), Phaeocystis globosa (8,11,16,(31)(32)(33), and Skeletonema costatum (34)(35)(36)(37), few studies have reported bacteria with algicidal effects against P. donghaiense. Therefore, an effective biocontrol method for the prevention and dissolution of P. donghaiense algal blooms must be developed.…”
mentioning
confidence: 99%
“…DNA of the isolates was extracted by using the CTAB method (Wilson, 2003). The 16S rDNA fragment was amplified by PCR (polymerase chain reaction) using primers 27f(5'-GAGAGTTTGATCCTGGCTCAG-3') and 1495r(5'-CTACGGCTACCTTGTTACGA-3') (Yang et al, 2015;Arimurti et al, 2017) employing 40 cycles of the following program: denaturation at 95 °C for 20 sec, annealing at 55 °C for 30 sec, and an elongation at 72 °C for 90 sec. Finally, it was followed by a final elongation at 72 °C for 5 min was performed.…”
Section: Identification and Biochemical Analysis Of Selected Caffeine-degrading Bacteriamentioning
confidence: 99%